Isomorphic (Koebner) Phenomenon Induced by Insulin Analogue Injections in Psoriasis. Issue 1 (30th November 2022) - Thijs, Saartje; Balti, Eric; Degraeve, Corinne; Coremans, Peter
Abstract: Koebner phenomenon is an uncommon skin-related complication of subcutaneous insulin injection in patients with diabetes mellitus. This reaction, also referred as isomorphic phenomenon, has previously been described in various conditions including vitiligo, lichen planus, and psoriasis. We report a 56-year-old woman insulin-treated patient with type 2 diabetes mellitus who developed new-onset, sharply well-demarcated erythematous scaly plaques at the insulin injection sites consistent with Koebner phenomenon. These lesions occurred after withdrawal of methotrexate initiated for the treatment of psoriasis. The lesions responded well to guselkumab, an interleukin-23 targeting agent but not ciclosporin. Of note, unlike previously reported cases, our patient developed isomorphic response under treatment with insulin analogues and during psoriasis flare-up. This case highlights the paramount role of thorough and cautious examination of injection and insertion sites in patients at risk undergoing subcutaneous continuous glucose monitoring or treated with continuous transdermal/subcutaneous insulin injections.